Proposta para integrar os sistemas de gestão da qualidade, das boas práticas de fabricação e da APPCC em uma pequena empresa de sucos de frutas. - Carrizo, Alberto (Universidade Federal de São Carlos, 2005)
The steady growth of the fruit juices sector is a significant factor strengthening the Brazilian economy; the richness of the tropical fruits, the quality of juices they are processed into and the luring presentation to consumers expanded the internal market and helped conquer demanding markets abroad. All this happened as a result of meeting stringent and assorted requirements, since food fruit juices included quality and safety are a must today. The purpose of this paper is to present a proposal to integrate management systems involving quality, good manufacturing practices and related legal requirements, as well as HACCP, in a small fruit juices company in the State of São Paulo. The proposal includes integrated cost-effective actions to implement the various standards. The research carried out concludes that the integration of management systems involving quality, good manufacturing practices and related legal requirements, as well as HACCP, is feasible. A relationship matrix of the respective requirements was designed during the research, which allowed conducting an initial joint and revealing assessment to evaluate the degree of fulfillment of those requirements. Bearing in mind the company´s scenario where the research was performed and the first application of this Integrated Management System took place, the proposal was not totally implemented. The necessity was perceived to test the Integrated Management System and monitor its operation in other food sector companies, thus not only evaluating the consistency of the proposal but also its flexibility to meet local specific requirements and detect improvement opportunities.
Keywords: Gestão da qualidade; Sistemas integrados; APPCC; Boas práticas de fabricação; ISO 9001; Legislação; Food quality; Food safety; GMP; ISO 9001 (2000); HACCP; Act RDC 275/01; Juice industry; Integrated management system; ENGENHARIAS::ENGENHARIA DE PRODUCAO